2018
DOI: 10.1039/c8cy01782d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of the ceria supported, re-catalyzed deoxydehydration of vicinal OH groups

Abstract: Deoxydehydration (DODH) is an emerging biomass deoxygenation process whereby vicinal OH groups are removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 59 publications
3
52
0
Order By: Relevance
“…While previous studies focused on organometallic catalysts, the authors tested the process in the presence of perrhenate (ReO 4 À ). Xi et al [30] performed a detailed mechanistic study of a ceria-supported Re catalyst with Pd, which catalyzes the H 2 spillover as an efficient hydrogenation catalyst. [31] Among the studies on selective dehydroxylation, most focused on DODH of short-chain vicinal alcohols with homogeneous Re catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies focused on organometallic catalysts, the authors tested the process in the presence of perrhenate (ReO 4 À ). Xi et al [30] performed a detailed mechanistic study of a ceria-supported Re catalyst with Pd, which catalyzes the H 2 spillover as an efficient hydrogenation catalyst. [31] Among the studies on selective dehydroxylation, most focused on DODH of short-chain vicinal alcohols with homogeneous Re catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…ReO x ‐Pd/CeO 2 catalyzed the DODH and subsequent hydrogenation of C=C bonds, such as erythritol to 1,2‐ and 1,4‐butanediols (1,2‐ and 1,4‐BuD), methylglycosides with cis ‐OH groups to the corresponding dideoxy products, and so on . Au or Pd promoters have the function of activating H 2 , and the activated hydrogen can move on the CeO 2 surface to enable the reduction of Re species in the reaction . Although Pd is a more effective promoter for H 2 activation, Pd is also active for C=C hydrogenation and thus the product over ReO x ‐Pd/CeO 2 becomes saturated.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Au or Pd promoters have the function of activating H 2 ,a nd the activated hydrogen can move on the CeO 2 surface to enablet he reduction of Re speciesi nt he reaction. [19][20][21][22][23][24]29] Although Pd is amore effective promoter for H 2 activation,P di sa lso active forC =Ch ydrogenation and thus the product over ReO x -Pd/CeO 2 becomes saturated. 1,4-Anhydroerythritol (1,4-AHERY), which can be easily obtained from erythritol by dehydration, is often used in the DODH reaction because of its high reactivity toward DODH [14, 15, 19-23, 30, 31] and its origin from biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, Re speciation is truly complex in solid catalysts; the simultaneous presence of various Re species and their relatively facile interconversion in the presence of reductants and organic molecules makes it difficult to unequivocally determine the most relevant state of the Re species, especially under reaction conditions. A most recent theoretical work even found that the DODH activity on ReO x /CeO 2 (111) could be improved if a Re VII species (with higher activity than the Re VI species) could be stabilized (with the help of Pd in close proximity) under reaction conditions . Currently, it is perhaps only safe to conclude that more than one Re species may be responsible for the catalytic activity and some Re species is more of a promoter instead of serving a direct catalytic role.…”
Section: Deoxygenation Of Small Diols and Polyolsmentioning
confidence: 99%